Unspoken thresholds: exploring spatiality and invasion in Zoya Pirzad's Things We Left Unsaid and Vanessa Chan’s The Storm We Made - Jeslyn Sharnita Amarasekera*; Farivar, Marziyeh (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the context of architecture, spatiality signifies dichotomies of interior and exterior, domestic or private and public or social domains, which are socially and psychologically meaningful. In a similar thread, spatiality within the literary context draws on elements that create boundaries between internal and external spaces within a text. This paper delves into the interior and exterior spaces presented by Zoya Pirzad in Things We Left Unsaid and Vanessa Chan in The Storm We Made. With distinctive references made to racial and ethnic conflicts within the respective nations, this paper seeks to examine how the female characters within the margins of society are represented when encountering the invader. Additionally, through the examination of spatial divides, we explore the notion of the threshold as a tangible and intangible idea or construct, acknowledging the distinction between the interior and exterior domains presented in both texts. In both works, the threshold within the spaces occupied and the characters' identities become intelligibly connected through various encounters, thoughts, and decisions drawn. The findings of this paper ultimately emphasise how thresholds in works of fiction, like these two novels, create a sense of comfort, safety, belonging, and the consciousness of self within the created space, as characters jostle between the invasion of the established threshold and the restructuring of the ruined threshold.